Multisite musculoskeletal pain in the general population: a cross-sectional survey - Vitta, Alberto de; Maciel, Nicoly Machado; Bento, Thiago Paulo Frascareli; Genebra, Caio Vitor dos Santos; Simeão, Sandra Fiorelli Almeida Penteado (São Paulo Medical Journal, 2022)
BACKGROUND: Epidemiological studies focusing on multisite musculoskeletal pain have revealed that the prevalence of multisite pain is high in general populations. OBJECTIVE: To ascertain the prevalence of multisite musculoskeletal pain in the last 12 months and in the last seven days, in a population-based sample and investigate its association with demographic, socioeconomic, behavioral, reported morbidity and ergonomic variables. DESIGN AND SETTING: Cross-sectional population-based survey in Bauru, São Paulo (Brazil). METHODS: 600 individuals were interviewed. The following data were collected: participants’ characteristics, through a precoded questionnaire; physical activity level, through the International Physical Activity Questionnaire; and musculoskeletal symptoms, through the Nordic questionnaire. Descriptive, bivariate and Poisson regression analyses were performed. RESULTS: The prevalence of multisite musculoskeletal pain was 46.5% (confidence interval, CI 42.5 to 50.5) in the last 12 months and 26.1% (CI 22.8 to 29.8) in the last seven days. The variables associated with multisite pain in the last 12 months were female sex, presence of hypertension, diabetes mellitus or depression, watching TV more than three times a week and working in a seated position. Formerly smoking was a protection factor. The variables associated with multisite pain in the last seven days were female sex, age group 60 years and over, low income, presence of comorbidities of hypertension, diabetes mellitus or depression and working in a seated position. CONCLUSION: There was high prevalence of multisite musculoskeletal pain, which was associated with demographic, socioeconomic, work-related, electronic device-related and reported morbidity variables.